The Fauna of Ricardo Nixon School (2016): An Analysis from the Conceptual Metaphor Theory - Alarcón Hernández, Paola (2025)
The article aims to analyze the metaphors belonging to the animal domain identified in the novel Ricardo Nixon School (Geisse, 2016). The theoretical framework is based on the Conceptual Metaphor Theory and its relationship with literary studies. The analysis procedure consists of the following stages: labelling, grouping of metaphorical terms into source domains, linking source domain to target domain, and metaphor focus. The metaphors analyzed include STUDENTS ARE ANIMALS, THE TEACHER IS AN ANIMAL, AND WOMEN ARE ANIMALS. The analysis contributes to gaining an understanding of how, through conceptual metaphor, the degradation of the protagonist is constructed throughout their life and professional experience.